The effectiveness of prevailing plasma spray conditions in the synthesis of protective coatings - Vitas, Valincius; Grigaitiene, Viktorija; Marcinauskas, Liutauras; Valatkevicius, Pranas (International Conference on Plasma Surface Engineering, 2013)
Protective and catalytic coatings of different composition are widely used in diverse fields of industry including a modification of surface layers of constructional materials. Mechanisms of film formation in plasma spray processes are not investigated thoroughly. It is not determined how the parameters of process influence the quality, specific surface area, thickness and adhesion of coatings. Therefore the investigation of the influence of formation technology on structure and properties of protective ceramic coatings is the main objective of present work.